(untitled) (RuMoRes, 2013)
In this article, I discuss the use of elements of the canons of thenineteenth century opera in fictional audiovisual products in the fieldof popular and media culture. I argue that opera culture is seen,in this domain, as an important deposit of conventions, rituals andmeanings that are understood as “exoticisms” of an old Europe, thusbecoming semantization or observation and critical tools of socialbehaviours and norms.